Kết quả nghiên cứu bổ sung về hệ tầng Đồ Sơn tại bán đảo Đồ Sơn, Hải Phòng - Phương, Tạ Hòa; Khôi, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2007)
The results of additional invesitigation on the Do Son formation in Do Son peninsula, Hai Phong